Stabilization of expansive clay soil using shells based agricultural waste ash - Almuaythir, Sultan; Muhammad Syamsul Imran, Zaini; Muzamir, Hasan; Hoque, Md. Ikramul (Nature Publishing Group, 2025)
This study investigates the effectiveness of using various agricultural waste ashes—namely eggshell ash (ESA), clamshell ash (CSA), cockle shell ash (CKSA), and oyster shell ash (OSA)—for the stabilization of expansive clay soils (ECS). Laboratory experiments assessed the impacts of these ashes on the soil’s consistency limits, shrink-swell behavior, compaction properties, unconfined compressive strength (UCS), shear strength, and mineralogical and microstructural characteristics. The results demonstrated that the inclusion of agricultural waste ashes significantly improved the ECS properties by reducing plasticity from 29.6 up to 7.84%, increasing shrinkage limit from 15.55 to 33.06%, reducing free sweeling index from 57 to 39.66%, and enhancing UCS and shear strength from 114.64 to 1509.95 kPa. Microstructural analysis revealed the formation of cementitious compounds that contributed to a denser and more robust soil structure. This research highlights the potential of these waste materials in sustainable soil stabilization, supporting environmental conservation and infrastructure resilience while aligning with Sustainable Development Goals (SDGs).